Wireless pH‐motility capsule for colonic transit: prospective comparison with radiopaque markers in chronic constipation - Camilleri, M.; Thorne, N. K.; Ringel, Y.; Hasler, W. L.; Kuo, B.; Esfandyari, T.; Gupta, A.; Scott, S. M.; Mccallum, R. W.; Parkman, H. P.; Soffer, E.; Wilding, G. E.; et al. (Neurogastroenterology and motility, 2010)
Background  Colon transit (CT) measurements are used in the management of significant constipation. The radiopaque marker (ROM) method provides limited information. Methods  We proposed to validate wireless motility capsule (WMC), that measures pH, pressure and temperature, to ROM measurement of CT in patients with symptomatic constipation evaluated at multiple centers. Of 208 patients recruited, 158 eligible patients underwent simultaneous measurement of colonic transit time (CTT) using ROM (Metcalf method, cut off for delay >67 h), and WMC (cutoff for delay >59 h). The study was designed to demonstrate substantial equivalence, defined as diagnostic agreement >65% for patients who had normal or delayed ROM transit. Key Results  Fifty‐nine of 157 patients had delayed ROM CT. Transit results by the two methods differed: ROM median 55.0 h [IQR 31.0–85.0] and WMC (43.5 h [21.7–70.3], P < 0.001. The positive percent agreement between WMC and ROM for delayed transit was ∼80%; positive agreement in 47 by WMC/59 by ROM or 0.796 (95% CI = 0.67–0.98); agreement vs null hypothesis (65%) P = 0.01. The negative percent agreement (normal transit) was ∼91%: 89 by WMC/98 by ROM or 0.908 (95% CI = 0.83–0.96); agreement vs null hypothesis (65%), P = 0.00001. Overall device agreement was 87%. There were significant correlations (P < 0.001) between ROM and WMC transit (CTT [r = 0.707] and between ROM and combined small and large bowel transit [r = 0.704]). There were no significant adverse events. Conclusions & Inferences  The 87% overall agreement (positive and negative) validates WMC relative to ROM in differentiating slow vs normal CT in a multicenter clinical study of constipation.